(untitled) (Bangladesh Journal of Medical Science, 2019)
Background:Long term microvascular complications of DM includes: nephropathy, retinopathy, and neuropathy. Increased level of IL-6 and its polymorphism have been associated with diabetic nephropathy.The present study was designed to determine serum level of IL-6 and C/G polymorphism at − 634 position in the promoter region of IL-6 gene in patients with type 2 diabetes mellitus (T2DM) with and without nephropathy. Method: This comparative study was comprised of 164 subjects, divided into two groups of 82 subjects in each. The subjects who had diabetes for more than 5 years without nephropathy were labeled as group-I and the subjects who had diabetes for more than 5 years with nephropathy were labeled as group-II. IL-6 polymorphism was detected by RFLP and its level was determined by ELISA technique. Data was analyzed using SPSS 20.0. Results: In group-I, 14 (17.1%) patients had CC, 47 (57.3%) had CG and 21 (25.6%) had GG polymorphism. In group-II, 9 (11%) patients had CC, 69 (84.1%) had CG and 4 (4.9%) had GG polymorphism. Pearson’s correlation test determined significant association of IL-6 polymorphism (CC,CG,GG) in both the groups (p <0.001). In patients of CC polymorphism, median levels of IL-6 was high in group-I (4.2) as compared to group-II (3.2),whereas in patients of CG polymorphism, median levels of IL-6 was high in group-II (3.8) as compared to group I (3.7) while in GG polymorphism, median levels of IL-6 was same in both the groups. On comparison of IL-6 polymorphism and level of IL-6 there was no statistically significant difference between the two groups (p1=0.304, p2=0.425 respectively). Conclusions: Statistically significant difference in the frequencies of allele (CC,CG,GG) between two groups is pointing towards the protective role of GG allele as it was predominant in T2DM patients without nephropathy. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.741-747